(untitled) (Journal of Informatics Education and Research, 2025)
Technological innovations like blockchain, digital twin modeling, artificial intelligence (AI), the internet of things (IoT), and renewable energy sources can significantly enhance the integration of green infrastructure for sustainable development. Artificial intelligence-powered monitoring systems enable real-time data analysis, which can be applied to waste management, energy efficiency, and water usage optimization. Smart sensors that are based on the Internet of Things make it possible to undertake predictive maintenance and automated environmental monitoring, which in turn minimizes operational expenses. There is greater investment in environmentally friendly infrastructure as a result of blockchain technology’s capacity to guarantee transparency in green financing and carbon credit trading. metropolitan planners are able to simulate and optimize environmentally friendly metropolitan plans through the use of digital twin modeling, which ensures that these designs are resilient to climate change. In addition, the incorporation of renewable energy sources such as solar and wind power into smart grids not only enhances sustainability but also reduces reliance on fossil fuels. Using these state-of-the-art technologies can make green infrastructure projects efficient, scalable, and economical. In addition to addressing economic and environmental issues, these initiatives can promote long-term urban sustainability and resilience.